Features of Students' Experiences in Gaming Activity (Based on Group Board Games) - Olga V. Mitina; Rina V. Isakova (Peoples' Friendship University of Russia (RUDN University), 2022)
The problems of the game have long been relevant for many researchers and are considered from the perspective of various disciplines. In the modern era of digitalization, computer games have become widespread; they attract the attention and interest of both users and researchers. At the same time, "ordinary" board games in modern psychology are studied much less frequently and, mainly, on the example of chess. The purpose of this study is to identify changes in emotional states during and as a result of two board games that involve cooperative and competitive actions ( Imaginarium and Monopoly respectively) as well as to describe the nature of experiences of students in gaming activities, in particular, taking into account their personal characteristics. The study involved 62 students of higher educational institutions in Tashkent (Uzbekistan). To diagnose the emotional state of the respondents, we used the Method for Measuring Emotional Experience in Activity by D.A. Leontiev, and the Russian-language version of the Implicit Positive and Negative Affect Test (IPANAT) by O.V. Mitina et al. To measure personality traits, we used the Russian versions of the six-factor HEXACO-PI-R personality questionnaire by M.S. Egorova et al. and of the Dark Triad personality trait diagnostic technique by T.V. Kornilova et al. The results of the study, in general, demonstrate positive changes in the emotional state after gaming, regardless of the result and process. Both board games, in spite of their specificity, well increased the positive emotional background of the respondents. At the same time, it was found that the nature of the experience is related to the content of the gaming activity: the respondents more often experienced meaningfulness in the cooperative game Imaginarium and emptiness in the competitive game Monopoly .